Escola Municipal Rural Maringá, em Araguatins - TO: um estudo de caso qualitativo dos processos e necessidades de formação docente - Alencar, Ricardo Lopes de (2015)
This master dissertation deals with the situation of teachers working in the Municipal Rural School in Maringa in Araguatins, region of Bico do Papagaio, northern Tocantins. We report the results of qualitative research case study type, triangulating data from questionnaires with questions of multiple choices, biographical accounts and accounts of field journal, bringing the processes and trajectories of teachers who work in a primary school in Rural School Araguatins TO and checking whether they met their real business needs, and if not, whether these teachers have sought other alternatives, in this case, punctuating them prospectively. Qualitative analysis of information allows us to raise significant issues in the search for solutions to problems on the quality of teaching and teacher performance of Brazilian rural schools. The theoretical framework is composed from authors researching on the of rural education in Brazil, standing out: Antunes (2012, 2013), Arroyo (2005), Hage (2006) and Molina (2006). The results show that the majority of teachers working at the school stands the indifference of the government towards the education field over the years, including the fact that the majority has no specific training to work in the rural education. Despite the universality and the protection of public laws and policies, highlighting the rural education as an educational mode, it is still subject to the decontextualization of a curriculum imposed by the city. This reality makes the education of uncharacteristic rural, totally alien to local reality, with textbooks related with other regions different of the local life. Aims to encourage the debate on educational institutions and curricula of teacher training courses, which should emphasize studies and reflections on the social, historical and cultural issues of the rural populations. The rural education has a link source with the peasant social struggles. In this process the teachers and educators of the rural has formed the own construction processes of rural education and how it can be enhanced pedagogically in specific training programs and policies. The case study presents an educational reality and oblivious teacher training to that question, regardless of whether it is a rural school established within an agricultural settlement, originating in a social movement of rural workers.